The Effect of Hypnobreastfeeding Techniques on the Process of Breast Milk Expulsion in Postpartum Mothers - Wati, Puri Kresna; Maghfira, Aisha Tamara; Nisa, Hainun (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Background: Exclusive breastfeeding for infants is important for their growth and development. Maternal and psychological factors in breastfeeding greatly influence the breastfeeding process and milk production. Feelings of stress, anxiety and pressure experienced by a mother can inhibit milk production. Several methods have been developed including the Hypnobreastfeeding technique. Hypnobreastfeeding helps mothers to ensure that they can continue to provide breast milk to the baby.Research Objective: To determine the effect of Hypnobreastfeeding technique on the process of breast milk production in postpartum women.Research Methods: Pre-experimental type of experimental analytics with a pretest- posttest one group design approach, namely in this paradigm there is a pretest before being given treatment so that the treatment results can be known more accurately.Research Results: Before being given the Hypnobreastfeeding Technique, the average breast milk volume was 60.50 ml and after being given the Hypnobreastfeeding Technique, the average breast milk volume was 98.40 ml.Conclusion: The results of the paired t-test conducted on the treatment group showed that the p value was 0.0001 (p<a), so there was a significant difference between the volume of breast milk before and after the Hypnobreastfeeding Technique treatment.Suggestion: It is hoped that it can make the latest innovation program about the world of Hypnosis not only Hypnobreastfeeding, it can also be used during the process of hecting anesthesia, infusion installation, and others.